2020
DOI: 10.31033/ijrasb.7.5.38
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Natural and Petroleum Based Materials on the Growth Rate and Antibiotic Sensitivity of Pseudomonas aeruginosa

Abstract: Most of bacteria spend their entire lives buffeted by changing environmental conditions, depending on the surrounding circumstances, to adapt and survive these changeable conditions. Bacteria have global response systems that result in sweeping changes in gene expression and cellular metabolism. In this study, caffeine, nicotine, and petroleum based materials were used as stress factors to Pseudomonas aeruginosa, to evaluate their potential ability to induce growth rate and antibiotic resistance mutations. Bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The authors reported a significant increase in the exchange rate between the sister chromatid in addition to chromosome damage. These chemicals’ ability to cause genetic changes upon their penetration inside the cells could turn the cells to either become carcinogenic or transfer the faulty genes to future generations [ 50 , 51 ]. Exposure to bisphenol A, which can be absorbed through the skin, has been significantly linked to neurological and reproductive damage [ 52 ].…”
Section: Health Impact Of Conventional Polymer-based Materials In mentioning
confidence: 99%
“…The authors reported a significant increase in the exchange rate between the sister chromatid in addition to chromosome damage. These chemicals’ ability to cause genetic changes upon their penetration inside the cells could turn the cells to either become carcinogenic or transfer the faulty genes to future generations [ 50 , 51 ]. Exposure to bisphenol A, which can be absorbed through the skin, has been significantly linked to neurological and reproductive damage [ 52 ].…”
Section: Health Impact Of Conventional Polymer-based Materials In mentioning
confidence: 99%
“…This rapidly spread from Wuhan to other areas. The novel coronavirus was named as the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2, 2019-nCoV) due to its high homology (~80%) to SARS-CoV, which caused acute respiratory distress syndrome (AR-DS) and increased mortality during 2002(Abd El-Aziz & Stockand, 2020ِ ِAbdel Rahman et al, 2020;Ahmadifar et al, 2019;Allaq et al, 2020aAllaq et al, , 2020bAmalraj et al, 2017;Badr et al, Fig. 1: coronavirus disease 2019 https://www.warminsterclinic.co.uk/coronavirusprecautions Globally, at least 1.7 million deaths have been directly attributed to COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these articles seek to investigate the disease's epidemiological para-meters at various locations to disseminate critical information between both modelers and policy-makers for a timely control response to be imple-mented. This is particularly crucial as the current epidemic involves the new pathogenic (SARS-CoV-2), on which restricted knowledge exists of its infectivity and clinical profile (Abd El-Aziz & Stockand, 2020;ِ ِAbdel Rahman et al, 2020;Ahmadifar et al, 2019;Allaq et al, 2020aAllaq et al, , 2020bAmalraj et al, 2017;Badr et al, 2020;Bashir et al, 2020;Belouzard et al, 2012;Bredan et al, 2020;Chan et al, 2020;Daw, Zgheel, et al, 2020;Elhadi & Msherghi, 2020;Group, 2020;Grzanna et al, 2005;Hassan et al, 2020;Horby et al, 2020;Kembuan et al, 2020;Ksiazek et al, 2003;Lashkari et al, 2020;Li et al, 2020;Lu, 2020;Millet & Whittaker, 2014;Motlagh et al, 2020;Ou et al, 2020;Pan et al, 2020;Pastick et al, 2020;Rizk et al, 2020;Rouf et al, 2020;Tomazini et al, 2020;Walls et al, 2020;Wang et al, 2020;Wiersinga et al, 2020;F. Wu et al, 2020;Z.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations